DISRUPTION OF CONTINUITY OR BUSINESS AS USUAL?: A SECTORAL ANALYSIS OF THE IMPACT OF COVID-19 ON EQUITY MARKETS IN BANGLADESH - Khatun, Mahfuza; Siddiqui, Sikandar (International Journal of Accounting & Finance Review, 2022)
The present paper analyses the impact of the COVID-19 breakout on the frontier stock market Dhaka Stock Exchange (DSE), exemplified by the case of Bangladesh. This study is based on secondary data from the official website of the Dhaka Stock Exchange. The sampling period extends across two sub-periods, referred to as the pre-lockdown period, extending from March 19, 2019, to March 25, 2020, and the re-opening period stretching from May 31, 2020, to March 11, 2021. Taken together, both sub-periods include a maximum of 442 data points. Our dataset consists of 106 listed companies from the Pharmaceutical, Engineering, and Insurance sectors in DSE. A classical Chow test was used to detect structural breaks. In a vast majority of cases, our results confirm the presence of structural breaks as an effect of Covid-19 by rejecting the null hypothesis. Our analysis of the statistical risk-return profiles of the companies under investigation indicates that the temporary interruption of stock trading in DSE was indeed a “game-changer”. Moreover, our findings support the view that pairwise return correlations tend to be larger during rapid market downturns than they are under “normal” or “positive” market conditions. JEL Classification Codes: C32, C58, G10.